Analysis of Brand Barriers and Its Impacts on SMEs Performance (Case Study of Dagadu and Batik Soenardi) - Widyastuti, Dominica A. (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2019)
The purpose of this study is to find out the brand development carried out by SMEs, the obstacles that occur, and the impact brand on SMEs performance. The in-depth interview method was carried out to the owners and managers of two SMEs in Jogjakarta namely Dagadu and Batik Soenardi. Interviews were conducted using a questionnaire as a guideline, with the intention of gaining an understanding of business practices and brand development processes. The data collection start from 15 November 2017 to 18 April 2018. Data obtained were analyzed using the within-case method, followed by cross-cases. Based on the research findings, it is known that the two SMEs have built brands through marketing strategies. The obstacles to SME brand development are limited human resources, intense competition, production and management. However, brand barriers do not significantly influence on sales, due there is a product uniqueness, which helps customers obtain the desired product.Keywords: Brand, Brand Development, Barriers of Brand, Performance of Brand, Small-Medium Enterprise (SMEs).Tujuan penelitian ini adalah untuk mengetahui pengembangan merek yang dilakukan oleh UKM, hambatan yang terjadi, serta dampak merek terhadap kinerja UKM. Metode wawancara mendalam dilakukan kepada para pemilik dan manajer dua UKM di Jogjakarta yaitu Dagadu dan Batik Soenardi. Wawancara dilakukan menggunakan daftar pertanyaan sebagai pedoman, dengan maksud mendapatkan pemahaman mengenai praktek bisnis dan proses pengembangan merek. Pengumpulan data dilaksanakan mulai 15 November 2017 sampai dengan 18 April 2018. Data yang diperoleh dianalisis dengan metode within-case, dilanjutkan cross-case. Berdasarkan hasil temuan penelitian, diketahui kedua UKM telah membangun merek melalui strategi pemasaran. Hambatan pengembangan merek UKM adalah keterbatasan sumber daya manusia, adanya persaingan yang ketat, produksi, dan manajemen. Meskipun demikian, hambatan merek tersebut tidak mempengaruhi kinerja merek itu sendiri. Kata Kunci: Merek, Pengembangan Merek, Hambatan Merek, Kinerja Merek, UKM